An optimal scheduling algorithm based on task duplication - Park, Chan-Ik; Choe, Tae-Young (IEEE transactions on computers, 2002)
Under the condition that the communication time is relatively shorter than the computation time for a given task, the task duplication-based scheduling (TDS) algorithm proposed by S. Darbha and D.P. Agrawal (1998) generates an optimal schedule. In this paper, we propose an extended TDS algorithm whose optimality condition is less restricted and where the length of the generated schedule is shorter than the original TDS algorithm.